Arrow's impossibility theorem: Two simple single-profile versions - Allan M. Feldman; Roberto Serrano (Brown University, Department of Economics, 2008)
In this paper we provide two simple new versions of Arrow's impossibility theorem, in a model with only one preference profile. Both versions are transparent, requiring minimal mathematical sophistication. The first version assumes there are only two people in society, whose preferences are being aggregated; the second version assumes two or more people. Both theorems rely on assumptions about diversity of preferences, and we explore alternative notions of diversity at some length. Our first theorem also uses a neutrality assumption, commonly used in the literature; our second theorem uses a neutrality/monotonicity assumption, which is stronger and less commonly used. We provide examples to illustrate our points.
Keywords: D60; D70; D71; 330; Arrow's theorem; single-profile; Unmöglichkeitstheorem; Theorie